The Impact of Digital Transformation on The Academic Work of Faculty Members at Bani Waleed University - Mohammed Abdo ulwahad AlSharaa; Salem Asseed Alatresh; Mohyaadean Atiya Mousa; K. Negrat (Journal of Scientific and Human Dimensions, 2026)
Digital transformation has become a defining characteristic of contemporary higher education institutions, reshaping academic roles, organizational structures, and teaching practices. This study aims to analyze the impact of digital transformation on the academic work of faculty members at Bani Walid University, focusing on workload, technological stress, organizational factors, and the experience of online teaching.The study adopted a mixed-methods approach with a sequential exploratory design. In the first phase, qualitative data were collected through semi-structured interviews with a purposive sample of faculty members to explore their experiences and identify key themes. Based on the results of this phase, a conceptual model was developed and quantitatively tested using questionnaire data from a sample of (N = 80) through structural equation modeling (SEM).The results showed that digital transformation leads to a significant increase in academic and administrative workload ((β = 0.55, p < 0.001), and contribute to higher levels of technological stress (β = 0.52, p < 0.001), especially in the context of weak infrastructure and a lack of training and technical support. Conversely, the results revealed a moderate positive impact of digital transformation on the e-teaching experience (β = 0.32, p < 0.05), reflecting opportunities to improve the quality of education despite the accompanying challenges. Institutional factors, such as digital infrastructure, organizational structure, and training, also play a crucial mediating role in shaping faculty experience. Furthermore, the results showed that technical expertise acts as a moderating variable, mitigating the negative impact of digital transformation on technological stress.The study confirms that digital transformation in higher education is not merely a technological shift, but a complex institutional process involving interwoven technological, organizational, and human dimensions. Therefore, the success of this transformation requires an integrated approach that balances infrastructure development, enhanced institutional support, and the development of faculty members' digital skills. These findings offer important insights for policymakers in designing effective and sustainable strategies for digital transformation in higher education.
Keywords: Digital Transformation; Faculty; Workload; Technological Stress; Higher Education; Structural Equation Modeling